Understanding parent experiences of end-of-life care for children: A systematic review and qualitative evidence synthesis. (February 2023) - Barrett, Laura; Fraser, Lorna; Noyes, Jane; Taylor, Jo; Hackett, Julia
Background: An estimated 21 million children worldwide would benefit from palliative care input and over 7 million die each year. For parents of these children this is an intensely emotional and painful time through which they will need support. There is a lack of synthesised research about how parents experience the care delivered to their child at the end of life. Aim: To systematically identify and synthesise qualitative research on parents' experiences of end-of-life care of their child. Design: A qualitative evidence synthesis was conducted. The review protocol was registered in PROSPERO (CRD42021242946). Data sources: MEDLINE, EMBASE, CINAHL, PsycINFO and Web of Science databases were searched for qualitative studies published post-2000 to April 2020. Studies were appraised for methodological quality and data richness. Confidence in findings was assessed by GRADE-CERQual. Results: About 95 studies met the eligibility criteria. A purposive sample of 25 studies was taken, of good-quality papers with rich data describing the experience of over 470 parents. There were two overarching themes: parents of children receiving end-of-life care experienced a profound need to fulfil the parental role; and care of the parent. Subthemes included establishing their role, maintaining identity, ultimate responsibility, reconstructing the parental role, and continuing parenting after death. Conclusions: Services delivering end-of-life care for children need to recognise the importance for parents of being able to fulfil their parental role and consider how they enable this. What the parental role consists of, and how it's expressed, differs for individuals. Guidance should acknowledge the need to enable parents to parent at their child's end of life.